2017
DOI: 10.9755/ejfa.2017.v29.i9.116
|View full text |Cite
|
Sign up to set email alerts
|

Bread quality improvement by means of selected pregelatinized waxy rice flour (PWRF)

Abstract: The objective of the present study was attempted to develop a pregelatinized waxy rice flour (PWRF) retarding agent formulation by merging with α-amylase and monoglycerides, as well as using pregelatinizing and lyophilizing technologies to improve bread characteristics such as staling and retrogradation. The major methods, including texture profile analysis (TPA) and sensory evaluation were employed to assess bread qualities. Research results demonstrated the amylose complexing index (ACI) of the PWRF-adding b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The improved texture of injera made from waxy sorghum (WHD1, WND1, WND2, WHD2, and WND3) was probably a consequence of the lower susceptibility of amylopectin to reassociation during retrogradation as compared with normal starch [10], and its better water-holding property as compared with amylose [7], which results in much slower starch retrogradation [11], producing slower staling and softer baked products [7]. The findings of this current study are in agreement with research on pan-type breads from different cereals where waxy barley starch [31], waxy wheat flour inclusion [12][13][14], and pregelatinized waxy rice flour addition [32] were found to produce softer breads and retard their staling. They are also in agreement with the observation of [33] of softer crumb texture in French bread when using wheat flours of low starch amylose content (15.4 to 16.6%).…”
Section: Descriptive Sensory Analysis Of Injerasupporting
confidence: 88%
“…The improved texture of injera made from waxy sorghum (WHD1, WND1, WND2, WHD2, and WND3) was probably a consequence of the lower susceptibility of amylopectin to reassociation during retrogradation as compared with normal starch [10], and its better water-holding property as compared with amylose [7], which results in much slower starch retrogradation [11], producing slower staling and softer baked products [7]. The findings of this current study are in agreement with research on pan-type breads from different cereals where waxy barley starch [31], waxy wheat flour inclusion [12][13][14], and pregelatinized waxy rice flour addition [32] were found to produce softer breads and retard their staling. They are also in agreement with the observation of [33] of softer crumb texture in French bread when using wheat flours of low starch amylose content (15.4 to 16.6%).…”
Section: Descriptive Sensory Analysis Of Injerasupporting
confidence: 88%
“…Generally, rice is classified into glutinous rice (amylose content < 5%) and nonglutinous rice (amylose content > 5%) (Nawaz et al., 2016). Because the sticky texture of glutinous rice flour, it is not commonly used in breadmaking unless hydrothermally or pregelatinized treatment (Yang et al., 2017). As for nonglutinous rice, plenty of studies showed that amylose content was the most vital factor and it is necessary to choose proper rice variety in breadmaking (Kang et al., 2009).…”
Section: Introductionmentioning
confidence: 99%